Projecting the future numbers of migrant workers in the health and social care sectors in Ireland - Alan Barrett; Anna Rust (The Economic and Social Research Institute (ESRI), 2009)
Ireland will experience population ageing in the coming years, whereby the percentage of the population aged 65 and over will rise from its current level of 11 percent to over 20 percent in 2035. A number of papers have looked at the implications of this process for the public finances. However, less attention has been paid to the human resource needs that will arise if increased demands are placed on health and social care systems. In this paper, we provide projections of the possible numbers that will be needed to work in the health and social care sectors out to 2035. We also consider what proportion of the extra employees will be migrants. We discuss both practical and ethical issues which arise when foreign health and social care workers are recruited.
Keywords: 330; Bevölkerungsentwicklung; Gesundheitsversorgung; Pflegeberufe; Ausländische Arbeitskräfte; Einwanderung; Prognose; Irland